(untitled) (Kronika Bydgoska, 2012)
The January Uprising (1863-1864) was the next, after the November Uprising (1830-1831), Polish national uprising in the 19lh century, finished with a defeat. Though formally, the events of the year 1863 were aimed at the Russian Empire and were fought in the (Congress) Kingdom of Poland and the Stolen Lands, this insurrection cannot be discussed separately from the political-social situation of the remaining sections of partitioned Poland. This insurrection incited many Poles, who were not indifferent to the fate of the broken motherland. The January Uprising had the biggest response in the Prussian section. Wielkopolska residents not only helped in weapons transport, but there were over 3,000 volunteers from the Prussian section in insurgent units. Also Bydgoszcz was taken into consideration in the insurgent plans of the Reds due to the key location on the routes of water and railway transport. However, the role of Bydgoszcz was not limited to a transit place.